Fish fauna of peatland waters in the middle Mahakam, Kutai Kartanegara, East Kalimantan, Indonesia - Suyatna Iwan (EDP Sciences, 2021)
A field study was carried out to collect fish from the lake and streams/rivers around the peatland from December 2020 to February 2021. Fishing gears such as gillnet, snakehead pole and line, lift net, trap net ("sawaran", "julu"), and fish pot ("tokong", "pangilar", "bubu" or "lukah" and "tempirai") were operated. Sampling sites, water velocities, and water depth were measured using GPS Garmin 60 CSX, current meter hydrologic velocity meter, and fishfinder Portable, respectively. Generally, water velocities of streams measured were much more rapid than the lakes ranging between 0.33 m/s (at water depth: 4.20 m) and 0,69 m/s (at water depth: 6.80 m); and "not detected" (at water depth: 2.40 m) and 0.34 m/s (at water depth: 1.20 m) respectively. Of 7,377 fish samples, there were 50 species discovered belonging to 19 families. Cyprinidae was the most populated in individuals and species as well (1,022 Ind.; 21 taxa). It was followed by Bagridae (63 Ind.; five taxa), Channidae (53 Ind.; three taxa), Clariidae (10 Ind.; three taxa), Siluridae (403 Ind.; three taxa), while other families had just one taxon. Diversity was observed higher in streams (35 species) than lakes (30 species). Local fishers are still performing unselective fishing for feeding fish cage culture.